Pregnancy-associated asymptomatic bacteriuria and drug resistance. Issue 3 (September 2015) - Khan, S.; Rashmi,; Singh, P.; Siddiqui, Z.; Ansari, M.
الملخص: أهداف البحث: يرتبط تجرثم البول بمخاطر ملحوظة للأم والجنين في الدول النامية. والظهور السريع لمقاومة المضادات الحيوية يستدعي الرصد المستمر لنمط المقاومة للعزلات البكتيرية. نعرض هنا النتائج التي توصلنا إليها حول العزلات البكتيرية لالتهاب المسالك البولية ونمط مقاومة الأدوية بين النساء الحوامل. طرق البحث: أجريت الدراسة على ١٣٥٨ سيدة حامل تراجع عيادة ما قبل الولادة بقسم أمراض النساء والتوليد، في الفترة بين يوليو ٢٠١٣م وأغسطس ٢٠١٤م. تم تجهيز عينات البول لعزل وتحديد أنواع البكتريا باستخدام الطرق الميكروبيولوجية القياسية. كما استخدم اختبار انتشار القرص لتحديد أنماط مقاومة مضادات الميكروبات للعزلات البكتيرية في المختبر المركزي لعلم الأحياء الدقيقة بكلية طب نيبال جونج، نيبال. النتائج: كانت ٣١٧ من العزلات موجبة للبكتيريا بشكل ملحوظ. كما لوحظت المقاومة للإريثرومايسين (٥٨.٦٪)، وكو-ترايموكسازول (٥٧.٤٪) وسيبروفلوكساسين (٥٠.١٪). كان ٢٠٣ من العزلات (٦٤٪) من السيدات في الفئة العمرية ٢١-٣٠ عاما وهذه المجموعة ذات دلالة إحصائية (قيمة ب <٠.٠٥) بالمقارنة للفئات العمرية الأخرى. الاستنتاجات: تجرثم البول منتشر بين السيدات الحوامل، مما يستدعي الفحص الروتيني بواسطة استنبات البول. الإشريكية القولونية كانت الجرثومة الأكثر شيوعا تليها الكلبسيلة الرئوية. وكانت السيدات من الفئة العمرية (٢١-٣٠) هن الأعلى خطورة. لا ينبغي استخدام الإريثرومايسين، وكو-ترايموكسازول وسيبروفلوكساسين تجريبيا كأدوية الصف الأول لعلاج التهاب المسالك البولية. الرصد المحلي المستمر لنمط المقاومة ضروري للاختيار المناسب للعلاجات المضادة للميكروبات. Abstract: Objectives: In developing countries, bacteriuria is associated with significant maternal and foetal risks. Rapid emergence of antibiotic resistance warrants continuous monitoring of the susceptibility patterns of bacterial isolates. In this study, we report our findings regarding the drug resistance patterns of bacteria isolates from pregnant women with urinary tract infections (UTI). Methods: This study included 1358 pregnant women attending the antenatal clinic at the Department of Obstetrics and Gynecology between July 2013 and August 2014. Urine specimens were processed for isolation and identification of bacterial species following standard microbiological methods. The disc diffusion test was used to determine the antimicrobial resistance patterns of the recovered isolates at the Central Laboratory of Microbiology of Nepalgunj Medical College, Nepal. Results: Three hundred and seventeen isolates were positive for significant bacteriuria. E. coli, K. pneumonia, P. aeruginosa, E. faecalis, S. aureus, P. mirabilis, CoNS, and P. vulgaris accounted for 61.5%, 17%, 7.5%, 5.3%, 2.8%, 2.5%, 1.8%, and 1.2% of bacterial isolates, respectively. Resistance to erythromycin (58.6%), co-trimoxazole (57.4%) and ciprofloxacin (50.1%) was observed. Among the 317 positive isolates, 203 (64%) were from women in the 21–30-year-old age group, and the rate of bacteriuria in this group was statistically significantly more than those for the other age groups ( P < 0.05). Conclusions: Bacteriuria is frequent among pregnant women, which generates a need for routine urine culture screening. In this study, E. coli was the most predominant bacterial species identified followed by K. pneumonia . Furthermore, women in the 21–30-year-old group were at a higher risk of UTI. Erythromycin, co-trimoxazole and ciprofloxacin should not be empirically used as first-line drugs in the treatment of UTIs. Continuous local monitoring of resistance patterns is necessary to determine the appropriate empirical antimicrobial therapy.